The Role of Instagram in Promoting Online Fashion at Vshopsidoarjo - Aini, Novi Nur; Hariyanto, Didik (Procedia of Social Sciences and Humanities, 2024)
This research examines the marketing communication strategy carried out by @Vshopsidoarjo via the Instagram platform, with a focus on the use of interactive features such as Instagram Stories. Based on the 4P marketing mix theory (product, price, promotion, place), this research explores how @Vshopsidoarjo utilizes social media to increase product marketing effectiveness, set competitive prices, expand market reach, and build closer relationships with consumers through interactive promotions . The research results show that this digital marketing strategy is successful in creating higher engagement with customers and increasing brand loyalty. The use of visual content and direct interaction through Instagram Stories has proven effective in building brand awareness and encouraging purchasing action. Overall, the use of social media as part of the marketing mix has had a positive impact on @Vshopsidoarjo's business growth.